On the nonkeys - Thi, Vũ Đức (Journal of Computer Science and Cybernetics, 2016)
In this paper we give some results about nonkeys. We show that for relation scheme the problem decide whether there is a nonkey having cardinality greater than or equal to a give integer m is NP-complete. However, for relation this problem can be solved by a polynomial time algorithm.